Sue & Tai-chan. 5 - Konami, Kanata, 1958- (Kodansha Comics, an imprint of Kodansha USA Publishing, LLC, 2024)
"Sue is an aging housecat who's looking forward to living out her life in peace ... but her plans change when the mischievous black tomcat Tai-chan enters the picture! Hey! Sue never signed up to be a catsitter"--